Effectiveness of virtual teaching programme regarding palliative care on knowledge, self-efficacy and attitude of Nursing Personnel in North India - Guleria, Alka; Rai, Kanika; Kumar, Yogesh; Sarin, Jyoti (Investigación y Educación en Enfermería, 2024)
Objective. To evaluate the effectiveness of Virtual Teaching (VT) Programme regarding palliative care on knowledge, self-efficacy and attitude among Nursing Personnel working in selected hospitals of North India. Methods. A quasi-experimental study with non-equivalent control group pre-test-post-test design was conducted on 121 Nursing Personnel, selected by convenient sampling technique. Knowledge, self-efficacy and attitude were assessed using structured knowledge questionnaire, Palliative Care Self-efficacy Scale, and Frommelt Attitudes toward care of dying scale respectively. Nursing personnel in experimental group received Virtual Teaching Programme regarding palliative care whereas those in comparison group received conventional teaching (CT). The study included a pre-test followed by the teaching (virtual/ conventional) on day one. The post-test was conducted on 15th day after the intervention. Results. The results showed that there was a significant difference in mean post-test knowledge (VT group: 17.11 to CT group: 25.05; t=9.25, p<0.001), self-efficacy (VT group: 39.27 to CT group: 43.38; t=6.39, p<0.001) and attitude (VT group: 108.86 to CT group: 133.23; t=9.27, p<0.001) scores between virtual teaching group and conventional teaching group. ANCOVA test revealed statistically significant differences in the mean scores of knowledge [F (1.11) = 86.61, p<0.001], self-efficacy [F (1.11) = 841.75, p<0.001] and attitude [F (1.11) = 82.92, p<0.001] between the groups, with higher means obtained in the CT group.